2018
DOI: 10.21767/2471-299x.1000073
|View full text |Cite
|
Sign up to set email alerts
|

The Using of "Guided Growth" for Correction of Coronal Deformities around the Knee in Skeletally Immature Children (Systematic review and Metaanalysis)

Abstract: Introduction: Angular deformities of the lower limbs are common during childhood. The concept of guided growth using a tension band plate is a breakthrough in the surgical correction of angular deformities. This approach has yielded satisfactory results and has low complication rates. Patients and methods:We reviewed 210 papers with overall 433 patients and 809 deformities. Inclusion criteria included papers published from 2010 to 2017 in English literature. A Meta-analysis was done on 16 papers with seven out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The total number of patients had open growth plates on preoperative radiographs. The underlying diagnoses included idiopathic femoral anteversion (3), internal tibial torsion (1), healed congenital pseudarthrosis of the tibia with NF-1 (1), and congenital femoral deficiency (1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of patients had open growth plates on preoperative radiographs. The underlying diagnoses included idiopathic femoral anteversion (3), internal tibial torsion (1), healed congenital pseudarthrosis of the tibia with NF-1 (1), and congenital femoral deficiency (1).…”
Section: Resultsmentioning
confidence: 99%
“…Hemiepiphysiodesis has evolved from the use of staples with perpendicular fixed legs to the use of a plate with pivoting screws [1]. The principle in both is to create a peripheral tether outside the physis, causing the physis to grow at its normal rate at the point farthest from the tether while limiting or temporarily stopping the growth at the point closest to the implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies mention physeal migration of the epiphyseal screw in guided growth as a complication of tension band plating, only two of which focus specifically on this complication; 15,16 the rest include screw migration together with other complications of guided growth with TBP. 4,14,18,19 One is a meta-analysis 20 and the other is a case report 13 (Table 4). Our results show a physeal migration rate of 5.91%; although higher than that of other studies, it is similar to the 5.88% rate reported by Heflin et al 18 and the 4% rate found by Ballal et al 4 and lower than the 7.7% reported by McClure et al 19 in knee flexion contractures, despite the fact that all these authors only describe one case each.…”
Section: Discussionmentioning
confidence: 99%